Identification of polymorphism on ND-5 mitochondrial DNA fragment of Benggala and Madura cattle with PCR-RFLP technique - NEO ENDRA LELANA; SUTARNO SUTARNO; NITA ETIKAWATI (Biodiversitas Journal of Biological Diversity, 2003)
The objectives of the research were to detect genetic variations on ND-5 region of mtDNA of Benggala and Madura cattles, and to compare the genetic diversity within or between Madura and Benggala cattle. Genetic variations and its effects on phenotype characters have been studied largely in dairy cattles, but not for beef cattles, especially for Indonesian local cattles. PCR-RFLP (polymerase chain reaction-restriction fragment length polymorphism) was used to detect polymorphism on ND-5 region of mitochondrial DNA. Polymorphisms were found on ND-5 mitochondrial DNA fragment using HindIII restriction enzyme. This variation were likely due to lost of HindIII restriction site on ND-5 mithocondrial DNA fragment.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: ND-5 mitochondrial DNA, genetic variation, PCR-RFLP.